Choque térmico no desenvolvimento in vitro de oócitos e embriões bovinos e estratégias para incrementar a qualidade embrionária - Ana Carolina Leite (2019)
Heat stress (HS) causes reduced fertility in bovine females, especially in dairy cows. Exposure to high environmental temperatures is known to adversely affect the quality and developmental competence of oocytes and embryos. Cytoprotective substances, when added to animal feed or embryo production media, can increase embryonic quality and resistance to injuries caused by heat stress. Supplementation of the bovine embryo culture medium with exogenous conjugated linoleic acid trans-10, cis-12 (CLA) can alter the lipid profile of embryonic cells, interfering with their developmental competence when exposed to adverse temperatures. The present work aims to explore determining factors of responses to the exposure of bovine oocytes and embryos to elevated incubation temperature, as well as to establish strategies to reduce heat stress damage to embryonic development. In experiment 1, the most appropriate concentration of Butyrolactone I (BUT-I) was tested to keep the oocytes in an immature stage, without compromising the resumption of meiosis later. Four concentrations of BUT-I (10µM, 25µM, 50µM and 100µM) were tested, comparing with immature oocytes (Immature Treatment) and matured oocytes (Control). The 50µM concentration of BUT-I proved to be more adequate in promoting reversible inhibition of meiosis, with rates of cleavage (92.5%) and embryo production (50.5%) higher than that found for the other concentrations of BUT-I (P <0.05; Cleavage rate 60.6%, 31.3% and 64.2% respectively for BUT10µM, BUT25µM and BUT100µM; Embryo production rate of 32.1% for BUT10µM, 17.6% for BUT25µM and 34.4% for BUT100µM) and similar to the control in oocytes submitted to embryo production after the end of the meiosis block. In experiments 2 and 3 oocytes and bovine embryos, divided into five treatments, were subjected to heat stress by elevation of the incubation temperature, at different stages of development. In Control, oocytes and embryos were cultured at 38.5ºC during all stages of in vitro embryo production (IVEP). In the germinal vesicle treatment (VG), oocytes were maintained for 12 hours in the germinal vesicle stage, by pharmacological induction with Butyrolactone-I (BUT-I) and, then, they were submitted to IVEP under conventional temperature conditions (38.5ºC). In the VGEC treatment, oocytes maintained in a germinal vesicle were exposed to thermal shock (41ºC for 12h) during pre-maturation and then subjected to conventional IVEP. In the MIVEC treatment, the oocytes were subjected to thermal shock during the first 12 hours of maturation (41ºC for 12h followed by 38.5ºC for 12h) and then subjected to fertilization and cultivation under thermoneutral conditions (38.5ºC). In the D7EC treatment, embryos with 144 hours post-insemination were subjected to 12 hours of thermal shock, followed by 12 hours of culture under conventional temperature conditions. Embryos produced from immature oocytes exposed to excessive heat (VGEC) showed less mitochondrial activity compared to embryos submitted to HS at the blastocyst stage (P <0.05), however it was shown to be similar to the Control and other treatments in the evaluated parameter. There was a reduction in the cytoplasmic lipids stocks in embryos from oocytes or embryos submitted to HS (number of lipid droplets 964.6; 1,484.2; 788.1 for treatments VGEC, MIVEC and D7EC, respectively) compared to treatments Control and VG (P <0.05). Regarding the percentage of the embryonic area occupied by lipid droplets, the VGEC treatment presented the lowest lipid content among the evaluated treatments (P <0.05;% embryo area occupied by lipids of 19.0% for Control, 15.4% for VG, 8.1% for VGEC, 16.5% for MIVEC and 17.1% for D7EC). Several morphofunctional changes related to quality, metabolism and embryonic implantation were found, such as ultrastructural changes in mitochondria and microvilli and an increase in cytoplasmic vacuolations. The VGEC treatment was the most affected by the thermal shock according to the parameters related to the embryonic development, presenting a reduction in the rate of cleavage, embryo production and hatching in relation to the Control (P <0.05). The results found show that oocytes from ovarian follicles in the early stages of growth are especially sensitive to damage caused by heat stress. In experiment 4, CLA was added to the in vitro culture medium in order to modulate the intracytoplasmic lipid deposition and increase the embryonic resistance to thermal shock. Embryos cultured in the presence of CLA showed lower lipids accumulation (P <0.05; average area occupied by lipids of 272,554.5; 301,960.7 and 413,124.9 for the CLA, CLA + SFB and Contole groups, respectively). However, the increase in embryonic quality was not enough to increase their survival, demonstrated by the superior embryonic reexpansion rate for the Control (70.4%) in relation to the SFB + CLA (43.3%) and CLA (47,1%). Oocytes and embryos subjected to heat shock experience important changes in the cytoplasmic dynamics and morphofunctionality of organelles such as embryonic mitochondria and microvilli that can be directly related to decreased embryonic survival after exposure to heat stress.